PERAN KADER POSYANDU DALAM PENDAMPINGAN IBU HAMIL RESIKO TINGGI TERHADAP PEMERIKSAAN KEHAMILAN SELAMA PANDEMI COVID-19 - Eny Susanti (NHM PRESS, 2020)
Antenatal care to pregnant women at risk is something that must be done at least 4 times during pregnancy to prevent harm to the mother and fetus during birth. The result of preliminary studies in october 2015, in Polindes Pajeruan there are 25 (21%0 of pregnant women experience high risk and in westwern Batuporo polindes 2 there were 19 (15%) of pregnant women experiencing high risk.. In this study, using analytical methods and cross sectional design